ANALISIS PENERAPAN SANKSI ADMINISTRASI PADA PELAKSANAAN PENGELOLAAN LIMBAH PADA RUMAH SAKIT UMUM RADEN MATTAHER JAMBI - Raharja, Ivan Fauzani (Faculty of Law, University of Palembang, 2018)
Medical waste is very important to manage properly, this is because medical waste belongs to the category of hazardous and toxic waste. Some of the medical waste is included in the category of hazardous waste and part of it is infectious. In relation to RSUD Raden Mattaher Jambi waste management problem, the ministry of environment giving black label in 2014 means that its waste management is very bad and it can affect the imposition of administrative sanction which will be accepted by RSUD Raden Mattaher Jambi. According to Article 198 of Government Regulation Number 101 Year 2014 on the Management of Hazardous and Toxic Wastes